TEACHING SPEAKING BY COMBINING CHORAL STRATEGY WITH SOCRATIC SEMINAR STRATEGY AT SENIOR HIGH SCHOOL - Seprianti, Hilda - (Pendidikan Bahasa Inggris, 2014)
This paper is talking about teaching speaking by combining socratic seminar strategy with choral strategy at senior high school which is aimed at discussing how to teach speaking by combining the two strategies. There are three stages of these strategies in teaching reading. Those are pre-speaking (exploration), while-speaking( elabration), and post-speaking (confirmation) in which divided in the following steps.(1)Teacher asks the students to stand in a circle and hand out copies of the text chosen (CS). (2)Teacher asks the students to read the text silently and tell them to read the text again (CS). (3)Teacher asks the students to practice or underline the important information on sentences, phrases, or words (CS). (4)Teacher asks the students to read again and asks them to give suggestions (CS). (5) Teacher asks the groups to read and represent the final summary of their work (CS). (6) Teacher asks the students to focus on their particular events or phenomenon that related with the topic in speaking class (SS). (7)Teacher asks the students to identify the description of their experience or phenomenon by using sequence of events in the past (SS). (8)Teacher asks the students to analyze the description of their experience before they practice in front of the class (SS). And (9) Teacher asks the students to practice their experience or retell a story in front of the class, so the teacher knows the studentsâ ability in speaking (SS).